Effect on Mechanical and Thermal Properties of Random Copolymer Polypropylene/Microcrystalline Cellulose Composites Using T-ZnOw as an Additive - Dan Cheng; Xiucheng Zhang; Siyu Wang; Lihua Liu (Advances in Polymer Technology)
Four-needle zinc oxide whisker (T-ZnOw) incorporated into microcrystalline cellulose/maleic anhydride grafted polypropylene/random copolymer polypropylene (MCC/PP-g-MA/rPP) composite was prepared by melt blending. 5 wt% PP-g-MA was used as a coupling agent to improve the interfacial compatibility between fillers and rPP. The effect of T-ZnOw on MCC/PP-g-MA/rPP composite was investigated by mechanical testing, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). Addition of T-ZnOw enhanced the mechanical properties of composites with tensile and flexural strengths increasing by 10% and 6%, respectively. SEM studies showed an improvement in the compatibility of fracture surfaces, which was evident from the absence of gaps between fillers and rPP. Additionally, initial thermal decomposition temperature and maximum weight loss temperature of T-ZnOw/MCC/PP-g-MA/rPP composite were both higher than those of MCC/PP-g-MA/rPP composite. Thermal degradation kinetics suggested that T-ZnOw has a weak catalytic effect on MCC, resulting in the early degradation of MCC and adhesion to the surface of rPP. Because of the presence of inorganic whiskers, the remaining weight percent was more than that of other composites at the end of the reaction. Crystallization temperature of the T-ZnOw/MCC/PP-g-MA/rPP composite was almost 3~5°C higher than that of MCC/PP-g-MA/rPP composite and close to the crystallization temperature of pure rPP.